MOLECULAR ASPECTS OF THE IMMUNOBIOLOGICAL STABILITY OF THE ORGANISM - Garkava, Katerina (Proceedings of National Aviation University, 2013)
The analysis of molecular mechanisms of regulation of immunobiological stability of the organism was carried out. Conclusion made that immunobiological stability of the organism requires consistency of lipid peroxidation, a range of lymphocyte receptors, interleukins and regulation of these processes by lymphocytic chalones system.